VEHICLE ROUTING PROBLEM WITH TIME WINDOWS USING HYBRID ENCODING GENETIC ALGORITHM - Chenniappan, Dr P.K; Devi, Mrs.S.Aruna (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
<!-- [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--> <!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--> The vehicle routing problem is to determine K vehicle routes, where a route is a tour that begins at the depot, traverses a subset of the customers in a specified sequence and returns to the depot. Each customer must be assigned to exactly one of the K vehicle routes and total size of deliveries for customers assigned to each vehicle must not exceed the vehicle capacity. The routes should be chosen to minimize total travel cost. Thispapergivesasolutiontofindanoptimumrouteforvehicle routingproblem using Hybrid Encoding GeneticAlgorithm (HEGA)technique tested on c++ programming.The objective is to find routes for the vehicles to service all the customers at a minimal cost and time without violating the capacity, travel time constraints and time window constraints